Study on Enterprise Industrial Property Value Evaluation—Take Huawei Company as an Example - Bo Feng , Shangen Xie, Junwen Feng (Forest Chemicals Review)
The evaluation of enterprise value is very important in enterprise management decision. The goal of corporate financial management is to maximize the value of the enterprise. With the continuous development of enterprises. As an indispensable part of enterprise value, industrial property value has become an important index to evaluate enterprise value to a certain extent. It is also an important embodiment of enterprise development and provides a reference basis for investors. This paper applies two methods to discuss the industrial property evaluation problem, one is the CAPM mothed, and another is the income method of asset appraisal. The capital asset pricing model (CAPM) is a finance theory that establishes a linear relationship between the required return on an investment and risk. The income method of asset appraisal, also known as income reduction method or income principal method, is one of the basic methods of asset appraisal recognized internationally. The influence factors of industrial property value is analyzed. The different assessment methods are discussed, and based on the optimal evaluation method, value approach is selected, and a case study of Huawei Company is given. This paper analyzes and studies the enterprise industrial property value evaluation index system. A systematic and comprehensive and scientific index system model is constructed, and a case study is analyzed and evaluated by using this model. This study provides a new way of thinking for business industrial property valuation. In addition, it is very necessary to determine the industrial property technology sharing rate and construct a detailed scientific weight index system.